Corporate Social Responsibility as a Dynamic Internal Organizational Process: A Case Study - Bolton, Sharon C. 1960-; Kim, Chung Hee; O’Gorman, Kevin D. (2011)
This article tracks Corporate Social Responsibility (CSR) as an emergent organizational process that places the employee at its center. Predominantly, research on CSR tends to focus on external pressures and outcomes leading to a neglect of CSR as a dynamic and developing process that relies on the involvement of the employee as a major stakeholder in its co-creation and implementation. Utilizing case study data drawn from a study of a large multinational energy company, we explore how management relies on employees’ interaction with CSR as the process of initiation → implementation → maturation develops. Employee involvement grows from a minor element in the CSR initiation stage to a vital contributory factor in CSR’s success in the later stages of the process. The article offers new insights into a processual and interactional approach to CSR that accounts for the actions of different actors involved at each stage. Most unusually, it also recognizes the dual impact this has on broader issues concerning the management and involvement of employees through CSR actions, and gaining legitimacy in the eyes of not only external stakeholders but internal too.
Keywords: CSR process; Stakeholder; Employee; Corporate social responsibility (CSR)